Early Cerebral Vein After Endovascular Ischemic Stroke Treatment Predicts Symptomatic Reperfusion Hemorrhage. Issue 7 (July 2018) - Cartmell, Samuel C.D.; Ball, Robyn L.; Kaimal, Rajani; Telischak, Nicholas A.; Marks, Michael P.; Do, Huy M.; Dodd, Robert L.; Albers, Gregory W.; Lansberg, Maarten G.; Heit, Jeremy J.
Abstract : Background and Purpose—: Parenchymal hemorrhage (PH) after endovascular mechanical thrombectomy in acute ischemic stroke leads to worse outcomes. Better clinical and imaging biomarkers of symptomatic reperfusion PH are needed to identify patients at risk. We identified clinical and imaging predictors of reperfusion PH after endovascular mechanical thrombectomy with attention to early cerebral veins (ECVs) on postreperfusion digital subtraction angiography. Methods—: We performed a retrospective cohort study of consecutive acute ischemic stroke patients undergoing endovascular mechanical thrombectomy at our neurovascular referral center. Clinical and imaging characteristics were collected from patient health records, and random forest variable importance measures were used to identify predictors of symptomatic PH. Predictors of secondary outcomes, including 90-day mortality, functional dependence (modified Rankin Scale score, >2), and National Institutes of Health Stroke Scale shift, were also determined. Diagnostic test characteristics of ECV for symptomatic PH were determined using a receiver operating characteristic analysis. Differences between patients with and without symptomatic PH were assessed with Fisher exact test and the Wilcoxon rank sum (Mann–Whitney U test) test at the 0.05 significance level. Results—: Of 64 patients with anterior circulation large-vessel occlusion identified, 6 (9.4%) developed symptomatic PH. ECV was the strongest predictor of symptomatic PH with more than twice the importance of the next best predictor, male sex. Although ECV was also predictive of 90-day mortality and functional dependence, other characteristics were more important than ECV for these outcomes. The sensitivity and specificity of ECV alone for subsequent hemorrhage were both 0.83, with an area under the curve of 0.83 and 95% confidence interval of 0.66 to 1.00. Conclusions—: ECV on postendovascular mechanical thrombectomy digital subtraction angiography is highly diagnostic of subsequent symptomatic reperfusion hemorrhage in this data set. This finding has important implications for post-treatment management of blood pressure and anticoagulation. Abstract : Supplemental Digital Content is available in the text.